Acute Kidney Injury Associated with Linagliptin. (14th February 2016) - Nandikanti, Deepak K.; Gosmanova, Elvira O.; Gosmanov, Aidar R.
Abstract : Linagliptin is a dipeptidyl peptidase-IV (DPP-IV) inhibitor that is approved for the treatment of type 2 diabetes mellitus. About 5% of linagliptin is eliminated by the kidneys and no dose adjustment is recommended in kidney impairment. We report a first case of linagliptin-associated acute kidney injury (AKI) in a patient with preexisting chronic kidney disease (CKD). We hypothesize that AKI was due to renal hypoperfusion from linagliptin-induced natriuresis and intravascular volume contraction in the setting of concomitant lisinopril use, which is known to impair autoregulation and potentiate hypotension-induced AKI. It may be prudent to exert caution and closely monitor kidney function when initiating linagliptin in combination with ACE-inhibitors in CKD patients.